The Respresentation Of Toxic Masculinity In The Power Of The Dog Movie - Tiara Putri Nurkinanti; Hidayati Hidayati; Bima Prana Chitra (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2024)
This study is about the idea of toxic masculinity as reflected in The Power of The Dog by Jane Champion based on the toxic theory of masculinity by Terry A. Kupers. In Kupers' theory, masculinity has toxic characteristics in the form of misogyny, wanton violence, aggression, and dominance. The researcher uses qualitative methods in conducting this research. Researcher focused on written data in the form of scripts from movie related to toxic masculinity. The researcher uses Jan Mukarovsky's dynamic structuralism approach. There is a relationship between toxic masculinity and hegemonic masculinity. There are many toxic masculinity traits that can be found in society. However, researchers limit the properties contained in the movie. The purpose of this study is society has knowledge about the characteristics of toxic masculinity and one factor of toxic masculinity. The results of this research contained 19 data which are characteristics of toxic masculinity and factors that cause toxic masculinity. Researcher found 4 (four) data covering the characteristics of misogyny, 2 (two) data on naughty violence, 6 (six) data on aggression, and 3 (three) data on dominance and 5 (five) factors to motivate toxic masculinity. The conclusion of this research is that the idea of toxic masculinity is not only dangerous for women but also for men. And the factor of the occurrence of toxic masculinity can also be due to trauma from the past.